2021
DOI: 10.1002/jcp.30300
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights: Dynamic foam cells derived from the macrophage in atherosclerosis

Abstract: Atherosclerosis can be regarded as a chronic disease derived from the interaction between disordered lipoproteins and an unsuitable immune response. The evolution of foam cells is not only a significant pathological change in the early stage of atherosclerosis but also a key stage in the occurrence and development of atherosclerosis. The formation of foam cells is mainly caused by the imbalance among lipids uptake, lipids treatment, and reverse cholesterol transport. Although a large number of studies have sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 162 publications
0
16
0
Order By: Relevance
“…Lipoproteins can be absorbed into macrophages and other cells through different transporters, which is called cholesterol uptake ( 111 ). In the 1970s, Brown and Goldstein laboratories demonstrated that modified LDLs were absorbed by macrophages via SRs ( 112 ).…”
Section: Regulation Of Foam Cells In Atherosclerosismentioning
confidence: 99%
“…Lipoproteins can be absorbed into macrophages and other cells through different transporters, which is called cholesterol uptake ( 111 ). In the 1970s, Brown and Goldstein laboratories demonstrated that modified LDLs were absorbed by macrophages via SRs ( 112 ).…”
Section: Regulation Of Foam Cells In Atherosclerosismentioning
confidence: 99%
“…In the pathological state of hyperlipemia, RCT function is affected, resulting in excess lipids accumulating in macrophages and inducing a subsequent inflammatory responsee. ( Sano et al, 2004 ; Li et al, 2020 ; Li et al, 2021 ). Lipid-derived macrophage inflammation will further stimulate the foaming of macrophages and increase the level of systemic inflammation by activating the nuclear factor κB (NF-κB) pathway ( Plotkin et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that ACAT1 is expressed in ERMCs. Intracellularly, ACAT1 is the only enzyme that catalyzes the connection of long-chain fatty acids with free cholesterol to form cholesteryl esters, which together with hydroxymethylglutaryl coenzyme A (HMG-CoA) synthase (HMGCS) and HMG-CoA reductase maintain and regulate the balance of intracellular cholesterol metabolism and play a key role in the development and progression of atherosclerosis ( Rusinol et al, 1994 ; Li et al, 2021 ). The StAR protein transports cholesterol to undergo steroidogenesis, where it binds to VDAC2 at the OMM to mediate cholesterol trafficking to the OMM ( Liu et al, 2006 ).…”
Section: The Function Of Endoplasmic Reticulum-mitochondria Contactsmentioning
confidence: 99%